DISTRIBUTIIN OF MARINE DEBRIS VARIATONS SPATIAL TO THE SEASONS AT THE CIREBON AND INDRAMAYU COASTALS - Ramadhan, Syahandra
Currently, marine debris poses a serious threat to the environment and human health. 80% of marine debris comes from land-based sources that can enter through rivers and drainage. Based on the assumption of the Ministry of Environment (KLH) in (Cordova, 2017) states that every day the Indonesian population produces 0.8 kg of waste per person or a total of 189,000 tons of waste / day. This study aims to see variations in waste distribution in 2 different seasons in the Cirebon and Indramayu Coastal Areas. It will also take into account the density, composition, influence of oceanographic conditions, and the influence of different environmental activities on the distribution of waste in the Cirebon and Indramayu Coastal Areas. In this study, samples were taken at several points along the Cirebon to Indramayu Coast that represent different environmental activities from each point. Waste samples will be classified by type and size based on guidelines from (KLHK, 2020). Overall, plastic waste is the most dominant waste found along the coast. Based on the results of field surveys in the second transitional season, waste was found on the Cirebon Coast with a total for all types of waste weighing 13,707 kilograms and on the Indramayu Coast weighing 6,989 kilograms. Meanwhile, for the west season in the Cirebon Coast, waste was found with a total weight of 24,636 kilograms for all types of waste while for the Indramayu Coast with a total weight of 20,941 kilograms. In general, the distribution of waste on the coast is influenced by many factors such as river flow that can carry waste from settlements, seasons that will affect rainfall and oceanographic conditions that can support waste transport, community activities, and types of waste related to the specific weight of waste that can be carried by water flow.